PLANNING IN THE MANAGEMENT SYSTEM - YEPIFANOVA, I.; DZHEDZHULA, V.; NADOLNY, O. (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The need for planning is caused by conditions of fierce competition, dynamic economic environment and changes in the market situation. The aim of the work is to systematize the approaches to determining the essence of planning and the sequence of implementation of the planning process at domestic enterprises.Approaches to defining the essence of planning are systematized. The existing approaches to the classification of planning methods are considered. The advantages and disadvantages of reactive and inactive planning are presented. The sequence of planning at domestic enterprises is generalized. The characteristic features inherent in strategic financial planning are generalized. It is determined that the optimization of planning decisions is to develop options for planned calculations to select the most optimal, which can meet such selection criteria as the maximum profit (income) per monetary unit of invested capital; saving financial resources, ie the minimum financial costs; current cost savings; minimum investment for the most effective result; maximum of the absolute amount of profit. The factors of the internal environment are summarized, which characterizes the potential of the enterprise, which must be taken into account in the planning process. The place of SWOT-analysis in the planning process is analyzed. It is determined that the planning process plays an important role in the enterprise management system, as it aims to form the goals of the enterprise (both strategic and tactical). The importance of strategic planning is emphasized.The generalization of existing approaches to determining the essence of planning has shown that the planning process involves the development and establishment of enterprise management system of quantitative and qualitative indicators of its development, which determines the pace, proportions and trends of the enterprise both in the current period and in the future.
Keywords: planning; plan; strategy; SWOT analysis